Racial and ethnic differences in risk of second primary cancers among breast cancer survivors - Calip, Gregory S. (Breast Cancer Res Treat, 2015)
PURPOSE: Disparities exist in breast cancer (BC) outcomes between racial/ethnic groups in the United States. Reasons for these disparities are multifactorial including differences in genetics, stage at presentation, access to care and socioeconomic factors. Less is documented on racial/ethnic differences in subsequent risk of second primary cancers (SPC). The purpose of this study is to evaluate the risk of SPC among different racial/ethnic groups of women with BC. METHODS: Retrospective cohort of 134,868 Non-Hispanic White (NHW), 17,484 Black, 18,034 Hispanic and 19,802 Asian/Pacific Islander (API) women with stages I-III BC in twelve Surveillance, Epidemiology and End Results Program registries between 2001–2010. Standardized incidence ratios (SIR), 95% confidence intervals (CI) and absolute excess risks were calculated by comparing incidence of SPC in the cohort to incidence in the general population for specific cancer sites by race/ethnicity and stratified by index BC characteristics. RESULTS: All women were at increased risks of second primary BC and acute myeloid leukemia (AML), with higher risk among more advanced stage index BC. Black and API women had higher SIRs for AML [4.86 (95% CI 3.05–7.36) and 5.00 (95% CI 3.26–7.32) respectively] which remained elevated among early-stage (I) BC cases. CONCLUSIONS: Women with a history of invasive BC have increased risk of SPC, most notable for second primary BC and AML. These risks for secondary cancers differ by race/ethnicity. Studies evaluating possible genetic and biobehavioral mechanisms underlying these differences are warranted. Strategies for BC adjuvant treatment and survivorship care may require further individualization with consideration given to race/ethnicity.